Antifungal Activity of Crude Extract from the Rhizome and Root of Smilacina japonica A. Gray. (15th July 2019) - Liu, Wei; Sun, Baozheng; Yang, Manman; Zhang, Ziyue; Zhang, Xiuxiu; Pang, Tingsong; Wang, Shengzheng
Abstract : This study aimed to investigate the antifungal activity of hydroalcoholic extract from Smilacina japonica A. Gray (SJA) against different fungi. The minimum inhibitory concentration (MIC) for SJA was determined by the broth microdilution method. The antifungal effects of SJA against Candida albicans were further confirmed by cell growth test and time-kill curve test. The effects of SJA on the fungal morphology and ultrastructure were also evaluated. SJA has a broad-spectrum antifungal activity. The MICs of SJA against different fungi, including fluconazole-sensitive and -resistant Candida albicans, other Candida species, and Cryptococcus neoformans, ranged from 208 μ g/ml to 1665 μ g/ml. Furthermore, SJA displayed fungicidal activity against varied fungi and obviously inhibited the hyphal growth of fungi. The mechanism study revealed that the antifungal activity of SJA might be associated with its effect on the cell morphology and ultrastructure.